"Łagodna" Fiodora Dostojewskiego w wizji filmowej Mariusza Trelińskiego = "A Gentle Creature" by Fyodor Dostoyevsky as a film vision directed by Mariusz Treliński - Mikiciuk, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article analyzes "A Gentle Creature" - a short story by Fyodor Dostoyevsky - as a film adaptationdirected by Mariusz Treliński, taking up the issue of intersemiotic translation. It also explores relationsbetween literature and film, such as narrative matters, time, space, the character concept and theways to express literary reality using cinematic methods. It brings up the social and cultural contextsin both mediums as well.
Keywords: Dostojewski, Fiodor Michajłowicz (pisarz rosyjski; 1821-1881); adaptacja filmowa